Non-steroidal anti-inflammatory drug naproxen destabilizes Aβ amyloid fibrils: A molecular dynamics investigation - Takeda, Takako (2010)
Using implicit solvent model and replica exchange molecular dynamics we examine the propensity of non-steroidal anti-inflammatory drug, naproxen, to interfere with Aβ fibril growth. We also compare the anti-aggregation propensity of naproxen with that of ibuprofen. Naproxen anti-aggregation effect is influenced by two factors. Similar to ibuprofen, naproxen destabilizes binding of incoming Aβ peptides to the fibril due to direct competition between the ligands and the peptides for the same binding location on the fibril surface (the edge). However, in contrast to ibuprofen naproxen binding also alters the conformational ensemble of Aβ monomers by promoting β-structure. The second factor weakens naproxen anti-aggregation effect. These findings appear to explain the experimental observations, according to which naproxen binds to Aβ fibril with higher affinity than ibuprofen, yet produces weaker anti-aggregation action.